ANALYSIS OF CONVERGENCE WITHIN THE EUROPEAN UNION SIGMA AND BETA CONVERGENCE - Begu Liviu-Stelian; Teodorescu Irina-Teodora; Dimidov Ioana-Catalina; Istrate Ionut (Annals of the University of Oradea: Economic Science, 2010)
Real convergence study began with the development of neoclassical models of growth and especially with the passage of econometric applications of these models. In this paper we present applications of indicators and patterns of convergence on the example of European Union member countries and some current economic impact assessments on European convergence process. This analysis is based on the estimated a- and b convergence and on Markov chains. The study deals with the economic convergence of the European countries and especially the convergence of the EU countries, including Romania. In the end of the study presents several economic scenarios for a faster and easier exit from the current crisis in Romania.